Waste Management in Buildings: Recycling Suggestions and Prevention of Carbon Emission Through an Education Building - Kara, Feride Çiğdem; Kayılı, Merve Tuna (Bartın Üniversitesi, 2021)
High-speed resource input is provided throughout the life cycle of the buildings that have a large share in energyand resource use. In the post-demolition phase where the service life of the buildings is over, when wastemanagement for the recovery of building components is not planned effectively, energy and resource inputs causeecological and economic losses. Especially today, the increase in buildings undergoing urban transformation putsthis problem forward. In this context, the waste management of an education building demolished in Karabük forthe protection and recycling of energy and resources included in the study was examined. As a result of theliterature review, suggestions for the recycling of large amounts of brick and ceramic wastes sent to landfills weredetermined. As a result of these recycling suggestions, the amount of embodied carbon that could be preventedfrom being released into the environment was determined. The importance of recycling the wreckage wastes, whichare determined to prevent the carbon emission of 220 tons of 601 kg CO2 eq for bricks and 8 tons of 41 kg CO2 eqfor ceramics, to the sector within the scope of the recommendations, has been stated in terms of energy and resourceconservation.

Enerji ve kaynak kullanımında büyük miktarda payı olan yapılara yaşam döngüsü boyunca yüksek hızda kaynak girdisi sağlanmakta ve hizmet ömrünün dolduğu yıkım sonrası evrede ise yapı bileşenlerinin geri kazanılmasına yönelik atık yönetimi etkin bir şekilde planlanmadığında enerji ve kaynak girdisi, ekolojik ve ekonomik kayıplara neden olmaktadır. Özellikle günümüzde kentsel dönüşüme uğrayan yapıların artması bu sorunu daha da öne çıkarmaktadır. Bu bağlamda, yapıya giren enerji ve kaynakların korunması ve geri dönüşümüne yönelik, Karabük'te yıkımı gerçekleştirilen bir eğitim yapısı üzerinden atık yönetiminin incelendiği çalışmada, yapılan literatür taraması sonucunda atık sahalarına gönderilen büyük miktardaki tuğla ve seramik atıklarının geri dönüşümüne yönelik öneriler belirlenmiştir. Sunulan bu geri dönüşüm önerileri sonucunda doğaya salımı engellenebilecek gömülü karbon miktarı tespit edilmiştir. Tuğla için 220 ton 601 kgCO2 eq, seramik için ise 8 ton 41 kg CO2 eq'nin doğaya salımının engellenebileceği tespit edilen yıkıntı atıklarının öneriler dahilinde sektöre kazandırılmasının, enerji ve kaynak korunumu açısından önemi belirtilmiştir.
Yapılarda Atık Yönetimi: Bir Eğitim Yapısı Üzerinden Geri Dönüşüm Önerileri ve Karbon Salımının Engellenmesi
Keywords: Environmentally Sustainable Engineering; Çevresel Olarak Sürdürülebilir Mühendislik